2022
DOI: 10.3390/ijerph19148794
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Salinity Changes under the Climate Change in the Khorezm Region, Uzbekistan

Abstract: Soil salinity negatively affects plant growth and leads to soil degradation. Saline lands result in low agricultural productivity, affecting the well-being of farmers and the economic situation in the region. The prediction of soil salinization dynamics plays a crucial role in sustainable development of agricultural regions, in preserving the ecosystems, and in improving irrigation management practices. Accurate information through monitoring and evaluating the changes in soil salinity is essential for the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The Bahamas and other countries are experiencing many negative impacts due to climate change. Regarding soil salinity, evapotranspiration is increased by climate change, which causes water to evaporate from the soil and increase the salinity levels (Khamidov et al 2022). On the other hand, there are many interventions that can be used to aid in the restoration of soil salinity levels.…”
Section: Comparison Of Soil Status Between 2020 and 2022mentioning
confidence: 99%
“…The Bahamas and other countries are experiencing many negative impacts due to climate change. Regarding soil salinity, evapotranspiration is increased by climate change, which causes water to evaporate from the soil and increase the salinity levels (Khamidov et al 2022). On the other hand, there are many interventions that can be used to aid in the restoration of soil salinity levels.…”
Section: Comparison Of Soil Status Between 2020 and 2022mentioning
confidence: 99%
“…Water shortage, soil salinity, and adverse climatic conditions are rising environmental problems in the country 24 . Soil salinity combined with water shortage and changing soil temperatures worsens the agricultural production in the country 25 , 26 . Indirectly, the quality of life is significantly degraded.…”
Section: Introductionmentioning
confidence: 99%
“…The study outcomes showed a decline in mildly salty soils but an increase in moderately and extremely saline soils. This highlighted that how crucial it is to comprehend how the climate affects soil salinity dynamics in order to implement appropriate regional management [23]. Consequently, the use of digital soil mapping and machine learning (ML) approach adopted by Taghizadeh-Mehrjardi et al, 2021, utilized the W-SVR (wavelet transformation with support vector regression) approach.…”
Section: Introductionmentioning
confidence: 99%